Energy, climate, and policy towards 2055: An interdisciplinary energy outlook (DIW-REM outlook) - Dawud Ansari; Franziska Holz; Hashem Al-Kuhlani (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
[Overview] This report presents a novel and independent energy outlook1 towards 2055. Similar to other prominent outlooks, such as the IEA's World Energy Outlook or the Royal Dutch Shell scenarios, our outlook illustrates possible global futures and provides readers with several insights on energy, climate, and interrelating fields. The outlook is the result of a three-year study by the research group Resource and Environmental Markets at the German Institute for Economic Research (DIW-REM). Its development has been part of research projects for the European Commission and the German Federal Ministry of Education and Research. The scenarios (to which we refer as 'narratives') depict the broad range of plausible developments in the years to come (cf. Figure 1). Each narrative starts in 2015 and describes a plausible (but not necessarily probable) path of the world towards 2055. Precisely, the outlook comprises the following four scenarios: * Business as Usual: A vision of the developments to happen if current trends are set to continue, i.e. the conflicting interests of various state and market actors in a tense (geo-)political environment lead to a diverse and ambiguous future energy system (which fails to curb emissions). * Survival of the Fittest: A worst-case vision of a world that disaggregates into various competing (regional) actors, who show only little regard to decarbonisation efforts and instead ramp up previous commitments in fossil fuels, eventually leading to a consolidation of power before large-scale climate catastrophes disrupt the world entirely. * Green Cooperation: A best-case vision of the revival of global cooperation and collaboration between different states and within them, which enables markets to allocate investments in the various technologies required to turn civilisation, society, and growth green. * ClimateTech: A surprise-case vision (wild card) of a technology-centred world in the aftermath of sudden advancements in various energy and climate technologies, which ultimately succeed in curbing emissions but fail to address the underlying social and economic structures preventing deep decarbonisation. [...]
Additional information: This report contains results from research projects for the European Commission and the German Federal Ministry of Education and Research ('SET-Nav', H2020 grant agreement no. 691843; 'FoReSee', BMBF Economics of Climate Change grant agreement no 01LA1811B).
Keywords: 330